Drop set versus traditional strength training protocols equated in volume on muscle thickness in women - José Vilaça-Alves; João Paulo Brito; Beatriz Machado; Rui Canário-Lemos; Tiago Moreira; Filipe Matos; Rafael Peixoto; Gabriéla Monteiro; Gabriela Lucas Chaves; Nuno Garrido; Filipe Casanova; Pablo B. Costa; et al. (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Purpose: The aim of this study was to investigate the effects of two strength training protocols, equated in volume, on the elbow flexor muscle thickness (MT) in women. Methods: Twenty-seven women (mean±sd, age 21.89±2.85 years; stature,167.82±5.90 cm; body mass 63.01±7.20 kg; estimate of body fat mass, 19.19±2.88%) were divided in three experimental groups: a drop-set (DS), a traditional (TR), and a control group (CG). The CG maintained regular strength training without perform any upper body exercises. The DS group performed a dumbbell biceps curl for two days/week, 12 weeks, 4 sets of 3 blocks of 10 repetitions at 75%, 55%, and 35% of their 1 Repetition Maximum (RM), and 8 sets of 11 repetitions at 75% of the 1RM for the TR protocol. Rest interval between sets was 120 seconds. The MT was acquired in the anterior face of both upper arms at 50% and 60% of the distance between the lateral epicondyle of the humerus and the acromial process of the scapula before (T0) and after the 24 training sessions (T1). Results: There was a significant increase in all MT measurements between T0 and T1for the training groups(p<0.05). In addition, significantly higher values of MT were found in the training groups compared to the control group for all local measurements in T1 (p<0.05). No significant differences were found between training the groups for MT. Conclusion: It appears that both training groups (DS and TR), were effective in promoting MT of the elbow flexors muscles of young women with no differences between training strategies.